Optimal Social Assistance and Unemployment Insurance in a Life-Cycle Model of Family Labor Supply and Savings - Peter Haan; Victoria L. Prowse (Institute for the Study of Labor (IZA), 2015)
We analyze empirically the optimal design of social insurance and assistance programs when families obtain insurance by making labor supply choices for both spouses. For this purpose, we specify a structural life-cycle model of the labor supply and savings decisions of singles and married couples. Partial insurance against wage and employment shocks is provided by social programs, savings and the labor supplies of all adult household members. The optimal policy mix focuses mainly on Social Assistance, which provides a permanent universal household income floor, with a minor role for temporary earnings-related Unemployment Insurance. Reflecting that married couples obtain intra-household insurance by making labor supply choices for both spouses, the optimal generosity of Social Assistance decreases in the proportion of married individuals in the population. The link between optimal program design and the family context is strongest in low-educated populations.
Keywords: J18; J68; H21; I38; 330; life-cycle labor supply; family labor supply; unemployment insurance; social assistance; design of benefit programs; intra-household insurance; household savings; employment risk; added worker effect